Фур’є спектроскопія газової фази СО та HF сумішей у середній інфрачервоній області - Sizhuk, A.S. (Publishing house "Academperiodika", 2012)
The gas phase spectra of hydrogen fluoride (HF) and carbon oxide (CO) mixtures are investigated using the Fourier transform infrared (FTIR) broadband spectroscopy technique for the region from 3838 to 3854 cm–1. The OC–HF complex bands, that can correspond to the excited intermolecular (complex) stretching and bending, are observed for the partial mixture pressures of 20 Torr of HF and 30 Torr of CO and higher. The corresponding hot bands of the second harmonic for the bending mode are observed at the total pressure of 100 Torr at –15 degree Celsius (corresponding to 26 Torr of HF and about 90 Torr of CO at room temperature). The observed hot bands are assigned with the help of the fitted spectra for a slightly non-rigid linear molecule. The fitting for the model linear molecule with the experimental data produced the following parameters for the excited states v1, v1 + v51 and v1 + v3: v1 = 3844.030345 cm–1 with B(v1}) = 0.104181 cm–1 and D(v1) = 3.447151 × 10–7 cm–1; v1 + v51 = 3931.406563 cm–1 with B(v1 + v51) = 0.105090 cm–1 and D(v1 + v51) = 3.31263 × 10–17 cm–1; v1 + v3 = 3960.722190 cm–1 with B(v1 + v3) = 0.102764 cm–1 and D(v1 + v3) = 3.059578 × 10–7 cm–1, respectively.